Frameworks of the European Union’s Policy Process 2017
DOI: 10.4324/9781315093994-2
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of multi-level governance: ‘Where Does It Come From? What Is It? Where Is It Going?’ *

Abstract: In two decades since the Maastricht Treaty, multi-level governance (MLG) has developed as a conceptual framework for profiling the 'arrangement' of policy-making activity performed within and across politico-administrative institutions located at different territorial levels. This contribution examines the ways in which the MLG literature has been employed, effectively taking stock of applied research to date. It identifies five main uses of MLG and the different focus of emerging research over time. Consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 44 publications
1
77
0
1
Order By: Relevance
“…Piattoni (2010, p.255) has suggested that multi-level governance (Marks, 1992), combining supra-state, national, and local or regional levels of control, now provides "the best single description and explanation of how the EU actually functions". Others (Stephenson, 2013) have argued that policy making within the EU is now too complicated to be contained within the three layers of multi-level governance and have sought to apply theories of network governance (Rhodes, 1996) whereby states and supra-state institutions are conceptualised as the activators of networks rather than the formulators of policy (Eising & KohlerKoch, 1999). Seddon (2014) has recently applied similar ideas to the specific area of the control of NPS.…”
Section: Discussionmentioning
confidence: 99%
“…Piattoni (2010, p.255) has suggested that multi-level governance (Marks, 1992), combining supra-state, national, and local or regional levels of control, now provides "the best single description and explanation of how the EU actually functions". Others (Stephenson, 2013) have argued that policy making within the EU is now too complicated to be contained within the three layers of multi-level governance and have sought to apply theories of network governance (Rhodes, 1996) whereby states and supra-state institutions are conceptualised as the activators of networks rather than the formulators of policy (Eising & KohlerKoch, 1999). Seddon (2014) has recently applied similar ideas to the specific area of the control of NPS.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, how can the quality of governance be ensured, and a measure of accountability to the public for governance failures by different actors be achieved? As submitted by Bache et al (2016, p. 489) but also by Stephenson (2013), MLG scholarship has so far shown (too) little concern for the (negative) implications of such 'complex and de-coupled governance processes' for democratic values and accountability. Papadopoulos (2007) points out that MLG's focus on 'managerial concerns of performance and efficiency' and the increased confederation of actors in diffuse, task-specific governance networks, without a clear overarching public decision-maker, means that the overall governance of important public interests (such as protecting persons in event of disasters) will become decoupled from public (democratic) control and accountability (also Stephenson, 2013, p. 826).…”
Section: Type I and Type Ii Mlgmentioning
confidence: 99%
“…The purpose of embedding this article in MLGliterature is not necessarily to 'test', reflect on or add to MLG-theory as such, but rather to use MLG as others have done: as a useful heuristic device to understand how disaster governance is 'arranged today in a way that [is] easy to grasp' and what challenges might arise from such arrangements (Stephenson, 2013, p. 818, emphasis removed). In fact, we are aware that MLG-literature has been criticized for its lack of engagement with explanations of causality, or with what drives MLG-regimes to come about in the first place (Stephenson, 2013). While we acknowledge such concerns and the importance of asking these questions, certainly as a matter of political science research, we also emphasize immediately that, as principally international legal scholars, we intend to use MLG predominantly in its more descriptive form as a way of understanding which levels or actors may be involved in disaster governance and how their activities may overlap or relate to each other.…”
Section: Introductionmentioning
confidence: 99%
“…Although potential policies will be formulated and developed at every governance level, the actors will increasingly engage with one another. As Stephenson (2013) argues, these policies will gradually become more and more entangled in a truly 'multilevel' governance fashion. However, as we show in this article, the mere presence of actors at different levels -that is, the presence of actors at 'multiple levels' of society -will not automatically result in 'multilevel' governance as traditionally formulated in the literature.…”
Section: Introductionmentioning
confidence: 99%